Pollen Cross-Reactivity: A Primer for Allergy Specialists (Actualité en allergologie et en immunologie au Canada, 2024)
There are over 400,000 land-based plant species that comprise our biodiverse habitat. Only a small subset of those plant species satisfies Thommen’s postulates, classifying them as allergens. The number of allergenic species, however, remains so vast that it is prohibitive to both test and treat for all relevant species within a geographical region. Allergy specialists have a valuable tool that can be used to help simplify the management of allergic patients: cross-reactivity. Cross-reactivity is the ability for an allergen to induce an IgE-mediated response, regardless of previous exposure. Allergens are a complex milieu of proteins, some of which have allergic potential while others do not. A number of proteins are conserved across allergen species. When exposure to these conserved proteins occurs, the immune system recognizes them in a similar manner. For homologous or cross-reactive allergenic proteins, this conserved molecular recognition initiates the allergic cascade. Allergen characterization is critical to the understanding of cross-reactivity. Characterization, in this context, refers to the protein make-up of a particular allergen. The process of allergen characterization began in 1962 with the discovery of antigen E, the first identified allergenic protein. Antigen E, commonly known as Amb a 1, is an allergenic protein in ragweed, and is the primary sensitizing protein for ragweed allergy sufferers. These primary sensitizers are referred to as major allergens and can be defined as such when >50% of the allergic patient population is sensitized to them. An entire branch of research arose from this discovery, which has allowed for major advances to be made in the understanding of cross‑reactive relationships among allergen species. Cross‑reactivity is not limited to homologous major allergen expression. Rather, minor allergens and panallergens, though less clinically relevant, play a similar role in cross‑reactive relationships. This primer will explore the science behind cross‑reactivity, as well as provide a general overview of the cross‑reactive relationships that have been defined for plant allergens found across North America.